Pediatric peanut aspirations before and after 2015 recommendation for early peanut exposure. (May 2023) - Greenlund, Lindsey; Borden, Amy; Nickel, Amanda; Arms, Joseph; Kavanagh, Katherine; McCoy, Jennifer; Shaffer, Amber; Snyder, Vusala; Tobey, Allison; Roby, Brianne
Abstract: Objectives: To investigate if there has been an increase in peanut foreign body aspirations (FBA) in children since the publication of the Learning Early About Peanut Allergy (LEAP) trial, which revealed that early exposure to peanut-containing foods prevented peanut allergies in children at risk of atopic disease. Methods: Retrospective chart reviews were conducted separately at two pediatric institutions. Institutions One and Two reviewed children less than 7 years old who underwent bronchoscopy for FBA over ten-year periods between January 2007 and September 2017 and November 2008 and May 2018, respectively. The proportion of FBAs attributed to peanuts was compared before and after the publication LEAP. Results: Out of 515 reviewed cases, there was no change in pediatric peanut aspirations prior to and following the LEAP trial and AAP guideline change (33.5% vs 31.4%, p = 0.70). At Institution One, 317 patients met inclusion criteria. When comparing FBAs before and after LEAP, there were no significant changes in the rate of peanut aspiration (53.5% vs. 45.1%, p = 0.17). Institution Two also found no significant increase in the rate of peanut aspirations before and after the Addendum Guidelines (41.4% vs. 28.6%, p = 0.65) upon review of 198 cases. Conclusions: Multiple institutions demonstrated a non-significant change in the rate of peanut FBAs following the AAP recommendation. Given that peanuts comprise a large proportion of FBAs, it is important to continue to track peanut aspirations. Longer term data tracking is needed from more institutions to further understand how recommendations from other specialties and the media impacts pediatric aspiration outcomes. Highlights: In 2015, the AAP encouraged exposure of children to peanut products early in life. We looked at peanut aspiration rates prior to and following these guidelines. There were no significant increases in peanut aspirations over the study period. Further data should be collected from other institutions and as more time passes.